Assessment of daily traffic counts to identify a typical day for data collection to estimate the annual average daily traffic - Reddy, Goney Vedha Prakash; Surachet Pravinvongvuth; Nakatsuji, Takashi; Kunnawee Kanitpong; Asian Institute of Technology Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2019)
Short period traffic counts (SPTC) are performed on the sites that do not have permanent traffic count (PTC) station. Traffic data collected from the SPTC are adjusted using the factors obtained from nearby PTC stations to estimate the annual average daily traffic (AADT). Accuracy of such AADT estimates depends on duration (n) and frequency (F) of SPTC. This paper tries to identify three practical aspects of SPTC scheduling, which are (i) how many days, (ii) how many times in a year and (iii) on which months should SPTC be performed? The analysis was carried out by applying Seasonal adjustment factors to the respective days{u2019} traffic counts to obtain the estimated AADT. Average errors of these estimates for different combination of days and months were calculated, the ranks were assigned simultaneously, and the sum of these ranks were considered to obtain generalized solutions that are expected to work well for all the sites located along the corridor. A real world dataset along the corridor of the third outer ring road in Bangkok, Thailand was used as a case study. The numerical results show that SPTC conducted once a year, on Wednesday and Thursday for 48-hour duration, in either month of January, February, or March will lead to the most reasonable estimation of AADT.
A research study submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Transportation Engineering
Research Studies Project Report (M.Eng.) - Asian Institute of Technology, 2019
Keywords: Traffic engineering -- Thailand -- Data processing; Traffic flow -- Thailand -- Bangkok